Caloric restriction improves perceived exertion while conserving immunity, fatigue, inflammation, and physical performance in male professional soccer players: a controlled randomized trial - Garcia-Morales, G; Díaz, G; Niño, A; del Campo, J; Tejero-González, C. (Journal of Human Sport & Exercise, 2025)
Purpose: In athletes, caloric restriction (CR) improves physiological mechanisms, although its effects on professional soccer players are unclear. This study aims to evaluate the effects of CR on physical performance, fatigue, and inflammation in male professional soccer players compared with a no-restriction diet.